Flexible grid connected inverter to enable single- and three-phase power processing with an integrated active ripple control unit - Rech, Thiago Fonseca (2021)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Elétrica, Florianópolis, 2021.